Economic transformation in Africa: Where will the path Lead? - Kolavalli, Shashidhara; Robinson, Elizabeth J. Z.; Diao, Xinshen; Alpuerto, Vida; Folledo, Renato; Slavova, Branimira; Ngeleza, Guyslain K.; Asante, Felix Ankomah (International Food Policy Research Institute, 2013)
This brief focuses on growth patterns, structural change and agglomeration to assess the progress of economic transformation in Ghana. While Ghana has been seen as a successful story in Africa because of its sustainable growth performance and impressive poverty reduction over the last two decades, Ghana’s economy has actually exhibited less transformation than might be expected for a country that has recently achieved low‐middle income status.